The influence of entrepreneurship education on entrepreneurial intention and entreprenur readiness at High School - Solikhah, Efa Wakhidatus; Puriyanto, Riky Dwi (Trigin Publisher, 2025)
Entrepreneurship education is an important strategy in fostering an entrepreneurial spirit among the younger generation, especially high school students. This study aims to analyze the effect of entrepreneurship education on the performance of entrepreneurial intention and entrepreneurial readiness of high school students. Using a quantitative approach with a survey method, data were collected through a questionnaire compiled based on indicators of entrepreneurship education, entrepreneurial intention, and readiness to run a business. The research sample consisted of high school students who had taken entrepreneurship lessons or programs. The results showed that entrepreneurship education had a positive and significant effect on both. The more effective the implementation of entrepreneurship education in terms of material, teaching methods, and practical experience, the higher the intention and readiness of students to become entrepreneurs. This finding emphasizes the importance of strengthening an applicable and contextual entrepreneurship curriculum at the high school level in order to prepare a young generation that is innovative, independent, and ready to create jobs.